EFFECT OF EARLY AMBULATION IN PATIENTS AFTER LOWER LIMB SURGERY: LITERATURE REVIEW - Faraniara, Faraniara; Maria, Riri (Universitas Respati Yogyakarta, 2020)
Early ambulation is one of the main goals of inpatient rehabilitation aimed at reducing the negative effects of immobilization and achieving functional recovery. Many studies have proven the benefits of early ambulation in patients after lower limb surgery so early ambulation is highly recommended as a form of orthopedic treatment. Although research related to the influence of early ambulation in post-operative patients has been widely carried out, it is necessary to do further study of the research article on the benefits of early ambulation. The purpose of this study was to look at the effect of early ambulation in patients after lower limb surgery. This literature study was made by analyzing nine scientific articles published in 2010-2020 and English language. Data obtained from the database include Proquest, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Google Scholar with keywords early ambulation, early weightbearing, lower extremity, lower limb and post-surgery. The results of this literature study found nine articles that fit the inclusion and exclusion criteria. The results of the study found that early ambulation in patients after lower limb surgery affected pain, complication rates, muscle strength and length of stay. Therefore, the results of the study of this literature can be a reference in assessments related to early ambulation in patients after lower limb surgery.